Gastrin releasing peptide receptor targeted nano-graphene oxide for near-infrared fluorescence imaging of oral squamous cell carcinoma - Ran Li (Nature Portfolio, 2020)
Abstract Oral squamous cell carcinoma (OSCC) is the most common malignant tumor that occurs in the oral mucosa. Pathological biopsy is still the current gold standard for OSCC diagnosis; however, some drawbacks need to be overcome. Therefore, it is urgently needed to find a non-invasive targeted technology for OSCC early diagnosis. Fluorescent optical imaging using near infrared (NIR) dyes tagged to tumor specific target will benefit such developments. Gastrin releasing peptide receptor (GRPR) is an attractive target for OSCC imaging and therapy. In this study, we synthesized nano-graphene oxide (NGO) nanoparticles with GRPR-specific peptides AF750-6Ahx-Sta-BBN via hydrogen bond and π–π bonds (NGO-BBN-AF750), and investigated their receptor binding, cell uptake and internalization in HSC-3 cells. NGO-BBN-AF750 and AF750-6Ahx-Sta-BBN showed a similar binding affinity to GRPR on HSC-3 cells. In contrast to AF750-6Ahx-Sta-BBN antagonist peptide, NGO-BBN-AF750 showed cellular internalization property. Overall, this study proposes a NGO nanoclusters-based nanoprobe for GRPR targeted near-infrared fluorescence imaging for OSCC. Nanoparticle-based delivery systems have shown highly significant potential in the delivery of a wide range of therapeutic agents.